IDENTIFICATION OF SPECIFIC SELECTION CRITERIA IN YOUNG BALL SPORT PLAYERS - Pucsok, József Márton; Ráthonyi, Gergely; Varga, Katalin; Perényi, Gabriella; Lenténé Puskás, Andrea; Bács, Zoltán; Balogh, László (Stadium - Hungarian Journal of Sport Sciences, 2020)
Background: Our study aimed to analyze body composition and spiroergometric data of young (14-15 years) elite level ball sport players. We suggested three-ball sports (handball, soccer, and basketball) share common performance indicators, as rapid intermittent movements primarily characterize each ball sport. Methods: We selected one-hundred and ten, handball (n=30), basketball (n=40), and soccer (n=40) players male and female from local clubs in Hungary. Seventy-nine males and thirty-one females participated in our study; their average age was 14.51 and 14.56, respectively. They participated in laboratory testing; the protocol included a body composition analysis and spiroergometric tests. We measured body composition and physiological parameters utilizing an In Body 720 device and a standard Bruce treadmill protocol. Although we were aware of the Bruce protocol limitations in elite athletes, we choose this protocol as a safer alternative for younger inexperienced athletes. Results and conclusions: We concluded that in young male soccer and basketball players, mean peak /load (W), peak/VE (l), peak/Vtex (l), peak/VO2 (ml/min), peak/VCO2 (ml/min), and peak/ O2 pulse (ml) data is a reliable indicator of the sport-specific performance. We may also suggest that in our male basketball and handball players’ population, peak/Vtex (l) is the only variable, which is significantly different. Between groups of male handball and soccer players, peak/VO2/kg (ml/min) may be a valid performance indicator. Among female basketball and handball players, we found a significant difference in three performance variables: peak/Vtex (l), peak/VO2 (ml/min), and peak/ O2 pulse (ml).